Ингерманландские финны: трудная история - Kirjanen, Alexander; Labudin, Alexander; Samodurov, Alexander (Administrative Consulting, 2025)
The subject of this study was been discussed in the previous article "Andropov and Karelia". The problem of the repatriation of Ingermanland Finns to Karelian-Finnish SSR is discussed in the article. This people were repressed during and immediately after the Second World war according of far-fetched charges with a crime. This problem is discussed in connection with difficult and tragic history of Ingermanland Finns people in centuries and especially in the twentieth century. The authors draw some actual conclusions for temporary state policy.